An experimental and kinetic modeling study of gas-phase autoignition of n-Pentadecane at low-to-high temperatures and elevated pressures. (1st March 2021) - Raza, Mohsin; Zhu, Jizhen; Zhong, Wenjun; Yuan, Feng; Yebing, Mao; Wang, Sixu; Lu, Xingcai
Abstract: In this study, low-to-high temperature oxidation of n-pentadecane (nC15 H32 ) is investigated in a rapid compression machine and a heated shock tube. The experiments are conducted at equivalence ratios of Φ = 0.5–2.0 with air as an oxidizer for the fuel-lean condition while diluted fuel mixtures for other equivalence ratios. A temperature range of 650–1450 K is investigated at a pressure of 6 and 10 bar in a rapid compression machine and a heated shock tube while a temperature range of 900–1350 K is investigated at a pressure of 15 bar in a heated shock tube. The fuel showed a two-stage ignition behavior which is a typical characteristic of large hydrocarbons and a negative temperature coefficient regime. The dependence of ignition delay times on pressure, equivalence ratio, and oxygen mole fraction are separately presented and discussed. The experimental results revealed the sensitivity of ignition delay times to all these factors. The available experimental data of C1 0 -C16 n-alkanes are compared which showed a small effect of chain length on the oxidation of alkanes. An updated reaction mechanism is presented after revising the rate constants of various reaction classes. The kinetic modeling predictions are compared and noticeable improvements are observed in the performance of the updated mechanism especially at low temperatures. The flux analysis is carried out to observe the fuel consumption along major low-temperature pathways. The sensitivity analysis is then performed to analyze the performance of the updated mechanism. To our knowledge, this is the first study on the autoignition of n-pentadecane.